(untitled) (Journal of Pure & Applied Sciences, 2023)
The objective of this study was to assess the impact of experimental factors on the volumetric properties and performance of warm mix asphalt (WMA) with RH-WMA using the Taguchi method. The gradations of the mixtures were based on AC 14, as specified by the Public Works Department of Malaysia. An L16 orthogonal array was employed to design the mixtures, considering three factors: compaction temperatures ranging from 95 to 140°C, RH-WMA contents ranging from 1% to 4%, and asphalt contents ranging from 3.5% to 6.5%. Sixteen mixtures were prepared according to the L16 array. The study focused on investigating several volumetric properties, including bulk-specific gravity, air voids, voids filled with asphalt, and voids in mineral aggregates. Additionally, the strength behavior of the samples was analyzed using the Taguchi method. The resilient modulus and performance of the mixtures were also evaluated. The results of the study indicate that a high RH-WMA content led to a slight decrease in the strength of the asphalt mixture and air voids. However, it increased the voids filled with asphalt (VFA) and resulted in softening of the asphalt mixtures.